2005
DOI: 10.2139/ssrn.678601
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Not Crisis: Medical Malpractice Claim Outcomes in Texas, 1988-2002

Abstract: Using a comprehensive database of closed claims maintained by the Texas Department of Insurance since 1988, this study provides evidence on a range of issues involving medical malpractice litigation, including claim frequency, payout frequency, payment amounts, defense costs, and jury verdicts. The data present a picture of stability in most respects and moderate change in others. We do not find evidence in claim outcomes of the medical malpractice insurance crisis that produced headlines over the last several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…We also observed that mean time to resolution for pediatrics cases increased significantly over our sample period, consistent with past findings. 4,22 Lengthy time to resolution Despite our ability to characterize annual rates of malpractice at the physician level (both unpaid claims and those resulting in indemnity) and to study patient factors associated with malpractice outcomes, our study had several limitations. As with other work, 23 our study used data from a single larger insurer.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that mean time to resolution for pediatrics cases increased significantly over our sample period, consistent with past findings. 4,22 Lengthy time to resolution Despite our ability to characterize annual rates of malpractice at the physician level (both unpaid claims and those resulting in indemnity) and to study patient factors associated with malpractice outcomes, our study had several limitations. As with other work, 23 our study used data from a single larger insurer.…”
Section: Discussionmentioning
confidence: 99%
“…is that there is no evidence of any skyrocketing compensation awards in medical malpractice cases (Black et al (2005), Vidmar et al (2005), Fenn et al (2000)); when plaintiffs go to court or appeal, the probability of compensation is generally lower but in the event of compensation being awarded, awards tend to be higher (Studdert and Mello (2007), Danzon (1985), Sloan and Hsieh (1990)); compensation amounts tend to increase with injury levels up to permanent grave injury (cases involving death usually receive lower payouts than these cases) (Sloan and Hsieh (1990), Vidmar et al (2005)). When it comes to the claim that the quantification of damages is random, the results are not always clear.…”
Section: "To Err Is Human"mentioning
confidence: 99%
“…Physicians concerned about rising insurance premiums may tend to blame plaintiffs, lawyers and juries rather than the exigencies of the underwriting cycle. The cause of periodic malpractice "crises," marked by sudden increases in malpractice insurance premiums, has been thoroughly studied, however, and is almost always due to cyclic changes in the insurance market 19,20 . Crises rarely occur because of significant increases in either the number of successful tort suits or the magnitude of jury awards 19 .…”
Section: The Policy Analyst's Perspectivementioning
confidence: 99%